Effect of No-Primers Orthodontic Adhesives on the Sheer Bond Strength of Meta Molar tubes Bonded to Porcelain: An In Vitro Study/Saeid Rahmani. - Rahmani, Saeid
General objective: The purpose of this in vitro study was to determine the shear bond strength of the universal orthodontic adhesive and the two no-primers orthodontic adhesives using the metal molar tubes bonded to porcelain surfaces conditioned with HFA surface preparation.